1996
DOI: 10.12693/aphyspola.89.335
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of MBE-Grown Cd1-xMnxTe Layers by Raman Spectroscopy

Abstract: In this paper we discuss a possibility of an optical characterization of thin semiconductor epilayers by Raman scattering measurements. As an example zinc blende Cd1-xMnxΤe epilayers (0.66 < x < 1.0) have been grown by molecular beam epitaxy method and investigated by Raman scattering and X-ray diffraction. Information resulting from both methods is compared and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
14
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 13 publications
4
14
0
Order By: Relevance
“…2). One-magnon structures found at the Raman spectra taken for these compounds at low temperatures can be compared with the earlier Raman scattering data obtained for MnTe and Cd 1 -x Mnx Te layers [5,6]. The observed composition dependence of the magnon frequency is quite similar in all three diluted AFIII systems.…”
supporting
confidence: 56%
“…2). One-magnon structures found at the Raman spectra taken for these compounds at low temperatures can be compared with the earlier Raman scattering data obtained for MnTe and Cd 1 -x Mnx Te layers [5,6]. The observed composition dependence of the magnon frequency is quite similar in all three diluted AFIII systems.…”
supporting
confidence: 56%
“…Such analysis at room temperature was previously performed on our samples and the results of these studies can be found in Ref. [3]. On the other hand, the structures observed in the -z(x, y)z polarization were previously not observed and we shall concentrate on discussion concerning possible physical mechanism responsible for this scattering.…”
mentioning
confidence: 69%
“…Magnetic excitations (magnons) were observed in the z(x, y)z polarization for thick layers of cubic MnTe at about 34 cm -1 at low temperatures [2]. The structures in the multilayer spectra are seen in the same polarization and, also, disappear at temperatures close to the Néel temperature in the bulk cubic MnTe.…”
mentioning
confidence: 91%
See 2 more Smart Citations